PERANAN APARATUR SIPIL NEGARA SEKRETARIAT DEWAN DALAM MEMBANTU PELAKSANAAN FUNGSI PEMBENTUKAN PERATURAN DAERAH DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN INDRAGIRI HULU TAHUN 2019-2020 - R Mhd Ramadhan Rafsanjani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The implementation of the duties and functions of the Sessions Division, such as the preparation of minutes of meetings, preparation of trial administration, as well as the preparation of meeting resumes and reports on the results of board meetings, is also considered to have not been maximally implemented efficiently and effectively. This study aims (1) to determine the role of the DPRD Secretariat ASN in supporting the function of forming regional regulations and (2) to find out the obstacles faced by DPRD Secretariat ASN in supporting the function of forming regional regulations of DPRD Indragiri Hulu Regency. The theory used in this study is 1. Active role, namely the role given by group members because of their position in the group as group activities such as administrators, officials or so on. 2. Participative role, namely the role given by group members to the group that makes a very useful contribution to the group itself and 3. Passive role, namely the passive contribution of group members. Data collection techniques used in this study were interviews and documentation. This research was conducted at the Regional House of Representatives (DPRD) of Indragiri Hulu Regency in 2019-2020. The results of the study indicate that the role of the DPRD Secretariat of Indragiri Hulu Regency in supporting the implementation of DPRD functions has been carried out effectively, judging from the success of implementing the programs and activities that have been determined. The role of the DPRD Secretariat of Indragiri Hulu Regency in supporting the implementation of DPRD functions has been carried out efficiently in terms of the use of the budget and the utilization of the potential of human resources for employees, as well as the level of timeliness of implementation and completion of assigned tasks. Keywords: State Civil Apparatus, Council Secretariat, Function for Formation of Regional Regulations